Answer to Question #250183 in Differential Equations for Wajid Ali

Question #250183
uxx= c^2ut by variable separation method
1
Expert's answer
2021-10-13T14:22:00-0400

We will solve the problem in next full description

1) Differential equation

"u_t=c^2u_{xx}" "0<x<l.\\space t>0"

2) Boundary conditions (zero conditions for example)

u(0,t)=0, u(l,t)=0;

3) Initial condition

u(x,0)="\\phi(x),0<x<l"

Solution:

Let u(x,y)=X(x)T(t) or have separeted variables.

Inserting this form in differential equation we have:

"X(x)T'(t)=c^2T(t)X''(x)"

Dividing both paths by "c^2X(x)T(t)" we have

"\\frac{1}{c^2}\\cdot \\frac{T'(t)}{T(t)}=\\frac{X''(x)}{X(x)}"

In this equation left part depend on t bur right part depend on x therefore both part are equal some constant which may be denoted as -"\\lambda"

Thus we have the system:

"x = \\begin{cases}\n T'+\\lambda c^2T(t)=0\\\\\n X''(x)+\\lambda\\cdot X(x)=0\n\\end{cases}"

Let we consider second eqution

"X''(x)+\\lambda\\cdot X(x)=0"

Boundary conditions at x=0 and x=l take the form:

X(0)=X(l)=0.

1) "\\lambda<0"

General solution of ode is "X(x)=C_1e^{-\\sqrt{-\\lambda}x}+C_2e^{\\sqrt{\\lambda }x}"

Then "X(0)=C_1+C_2=0" ,"C_2=-C_1"

Therefore "X(x)=C\\cdot (e^{-\\sqrt{-\\lambda}x}-e^{\\sqrt{-\\lambda}x})"

Condition X(l)=0 implies

"C\\cdot (e^{-\\sqrt{-\\lambda}l}-e^{\\sqrt{-\\lambda}l})=0" and hence C=0, therefore X(x)"\\equiv0"

but we need nontrival solution hence case "\\lambda<0" is impossible, case "\\lambda=0" is impossible too with similar argues, typical case is "\\lambda>0"

In this case "X(x)=C_1sin(\\sqrt \\lambda x)+C_2cos(\\sqrt \\lambda x)"

X(0)= "C_2=0=>" X(x)="Csin(\\sqrt \\lambda x)"

X(l)=0=>"sin(\\sqrt\\lambda l)=0=>\\sqrt \\lambda l=\\pi\\cdot n.n>0"

"\\lambda_n=\\left(\\frac{\\pi\\cdot n}{l} \\right)^2" and "X_n(x)=sin\\left(\\frac{\\pi\\cdot n\\cdot x}{l}\\right)"

For this "\\lambda_n" an equation "T'+\\lambda c^2T(t)=0" has solution

"T_n(t)=e^{-\\lambda_n\\cdot c^2\\cdot t}" and "u+n(x,t)=T_n(t)X_n(x)=e^{-\\lambda_nc^2t}sin\\left( \\frac{\\pi nx}{l}\\right)"

After that we search solution in the form

"\\sum_{n=1}^{\\infty}C_ne^{-\\lambda_nc^2t}sin\\left( \\frac{\\pi nx}{l}\\right)" for initial condition to satisfy.

Insertinf t=0 we have

"\\sum_{n=1}^{\\infty}C_nsin\\left( \\frac{\\pi nx}{l}\\right)=\\phi(x),0<x<l"

Then "C_n=\\frac{2}{l}\\int_0^l\\phi(x)sin\\frac{\\pi n z}{l}dz" -Fourier coefficients. With such coefficients solution of the problem is:

"\\sum_{n=1}^{\\infty}C_ne^{-\\lambda_nc^2t}sin\\left( \\frac{\\pi nx}{l}\\right)"


Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog